TATALAKSANA STOMATITIS ALERGICA PADA PENDERITA YANG MENGALAMI STRESS (Management of Allergic Stomatitisin Patient with Stress) - Raziv Ganesha; Diah Savitri E; Hening Tuti Hendarti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Introduction: Allergic stomatitisis ahypersensitivity reaction caused by allergens, such as drugs, food, and dental materials. Manifestation allergic reaction to food in oral cavity can be recurrent ulcer. Purpose: This case report pupose to report management allergic stomatitis in Stress condition.Case: female was a 44-year-old with complaintmany stomatitis in oral cavity. Patients say often since ± 6 years ago without knowing the cause. Stomatitis often moving location but also in the same site. On intra oral examination found ulcer multiple, variant size, irregular shape, paintfull.Management: the patient performed examination of total IgE with a result of 642.98 (normal<150), skin prick test in patients results positive on dust house, dog hair, cotton, beef, cow's milk, chicken egg yolk, shrimp, milkfish, pindang, chocolate, and peanuts.Patients given aloe vera extract oral rinse at the first visit, then after skin prick test was given methylprednisolone, hepaprotector caplet, multivitamin B-Complex plus Zinc. Patients are also given education and instruction to avoid a food become allergic. Conclusion: Allergic Stomatitis diagnosis requires a complete history and supportive examination. In this case, the treatment requires good cooperation between the patient and the dentist so that treatment can be done thoroughly.